Cultural perception of “pregnancy and childbirth” in the rural communities of the Ayaviri-Puno district - Calderón-Torres, Alfredo (2021)
Native and Amazonian communities have this tendency to consider pregnancy and childbirth as a cultural and historical process of self-determination. This section deals with traditional knowledge in relation to pregnancy and childbirth, which is still revalued and put into practice in rural areas, however, this knowledge is being displaced by modernity. The objective of the research is aimed at reassessing the cultural perception of "pregnancy and childbirth", linked to customs, beliefs, cultural tradition, the role of midwives and symbolic representations, as a millenary cultural manifestation; This study is qualitative, using the ethnographic design and inductive method. The results describe the customs and beliefs in relation to pregnancy and childbirth associated with food beliefs and importance of supernatural beings and deities; as well as, the popular tradition expressed in celebrations at the family and collective level; The role of midwives is also developed in the therapeutic treatment with plants, minerals and animals, and ultimately the ritual acts related to pregnancy and childbirth are analyzed, as a product of an ancestral cultural heritage still valued in the district's communities. from Ayaviri-Puno.